Measurement and prediction of compressive properties of polymers at high strain rate loading - Mohd Firdaus, Omar; Hazizan, Md Akil, Assoc. Prof. Dr.; Zainal Ariffin, Ahmad, Prof. Hj. (Elsevier Ltd., 2011)
Link to publisher's homepage at http://www.elsevier.com/